The third head of the biceps brachii muscle exhibiting variable shape presentation: Prevalence, variability and clinical considerations - Arthur Tsalani Manjatika; Joshua Gabriel Davimes; Pedzisai Mazengenya (Elsevier, 2024)
Introduction: The third head of the biceps brachii is the predominant variation of the arm muscles. Awareness of muscular variations is essential for the management of upper limb pathologies. Variations in the shape of the muscles are rarely explored. This study aimed to describe the prevalence and anatomical presentation of the third head of the biceps brachii muscle (origin, insertion and innervation) with an emphasis on the shape and form variations. Materials and methods: Biceps brachii of eighty-nine cadavers were examined. The presence of the third head, its origin, shape patterns, blood supply, and nerve innervation were determined and recorded. Results: The third head of the biceps brachii was present in 20.2 %, with a prevalence of 22.2 % in males and 18.2 % in females. Half (50 %) of these were bilateral presentations. Most (92 %) of the third head of the biceps brachii variations were flat, thin and straight in shape. All the shape variation patterns were observed in males and on the left arm. The third head originated from the humerus on its anteromedial aspect in 92 % of cases. The musculocutaneous nerve innervated the third head of the biceps brachii in 96 % of the cases, and a nerve anomaly of musculocutaneous and median nerves innervated it in a single (4 %) case. The muscular branches of the brachial artery supplied the third head of the biceps brachii in all cases. Conclusion: Studies on the variation of arm muscles may assist in identifying new patterns of morphological variations like the shape of the muscle and may aid in the accurate diagnosis and management of arm pathologies.